Correlation between Learning Readiness and Learning Motivation with Mathematics Learning Outcomes in SPLDV Material - Meli Lestari; Ahmad Yani; Revi Lestari Pasaribu; Zubaidah R; Rustam Rustam (JPMI (Jurnal Pendidikan Matematika Indonesia), 2026)
This study aims to determine the correlation between learning readiness and learning motivation with students' mathematics learning outcomes in the Two-Variable Linear Equation System (SLSDV) topic. This study used a quantitative approach with a correlational design. The population in this study were all eighth-grade students of SMP Takhassus Al-Qur'an Ngabang. The research sample was selected from classes VIII D and VIII E, totaling 57 students selected using simple random sampling. The instruments used in this study included a learning readiness questionnaire, a learning motivation questionnaire, and a descriptive test on the SLSDV material. Data analysis was performed using SPSS for Windows version 23 using the Pearson Product Moment correlation test and multiple linear regression. The results showed a positive and significant correlation between learning readiness and mathematics learning outcomes with an r value of 0.967, which is classified as very strong. Furthermore, there was a positive and significant correlation between learning motivation and mathematics learning outcomes with an r value of 0.849, which is classified as very strong. Simultaneously, there is a positive and significant correlation between learning readiness and learning motivation with mathematics learning outcomes with an R value = 0.983 which is classified as a very strong category and an Adjusted R2 value = 0.965 which means that 96.4% of mathematics learning outcomes can be explained by learning readiness and learning motivation, while the remaining 3.6% is influenced by other factors.Korelasi antara Kesiapan Belajar dan Motivasi Belajar dengan Hasil Belajar Matematika pada Materi SPLDVABSTRAKPenelitian ini bertujuan untuk mengetahui korelasi antara kesiapan belajar dan motivasi belajar dengan hasil belajar matematika siswa pada materi Sistem Persamaan Linear Dua Variabel (SPLDV). Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII SMP Takhassus Al-Qur’an Ngabang. Sampel penelitian dipilih kelas VIII D dan VIII E dengan jumlah sebanyak 57 siswa yang dipilih menggunakan teknik simple random sampling. Instrumen yang digunakan dalam penelitian ini meliputi angket kesiapan belajar, angket motivasi belajar, dan tes uraian materi SPLDV. Teknik analisis data dilakukan dengan bantuan software SPSS for Windows versi 23 menggunakan uji korelasi Pearson Product Moment dan regresi linear berganda. Hasil penelitian menunjukkan bahwa terdapat korelasi positif dan signifikan antara kesiapan belajar dengan hasil belajar matematika dengan nilai r = 0,967 yang tergolong ke dalam kategori sangat kuat. Kemudian, terdapat korelasi positif dan signifikan antara motivasi belajar dengan hasil belajar matematika dengan nilai r = 0,849 yang tergolong ke dalam kategori sangat kuat. Secara simultan, terdapat korelasi positif dan signifikan antara kesiapan belajar dan motivasi belajar dengan hasil belajar matematika dengan nilai R = 0,983 yang tergolong ke dalam kategori sangat kuat serta nilai Adjusted R2 = 0,964 yang berarti bahwa sebesar 96,4% hasil belajar matematika dapat dijelaskan oleh kesiapan belajar dan motivasi belajar, sedangkan 3,6% sisanya dipengaruhi faktor lain.Kata Kunci :Kesiapan belajar; motivasi belajar; hasil belajar matematika